Tourism Planning in Developing the Tourism Potential of The Pusuk Buhit Area in Samosir Regency - Siti Hajar; Ribut Priadi; Agung Saputra (Publik : (Jurnal Ilmu Administrasi), 2022)
The grouping of existing tourism potential in the Pusuk Buhit area must be carried out in several stages of assessment or measurement as described in the Regional Long-Term Medium-Term Plan (RPJMD) of Samosir Regency for 2016-2021. the need for tourist facilities and tourist attractions of interest. The development of tourism potential carried out in the Pusuk Buhit area has not been realized optimally due to the incompatibility of grouping and planning in the development of tourism areas. The purpose of this study is to identify and analyze the tourism potential that can be developed in the Pusuk Buhit area through tourism planning. The analysis used in this research is qualitative analysis. The result of this research is the existence of tourism potential in the Pusuk Buhit area that can be mapped so that it can be developed according to the planning perspective and can realize superior and competitive tourism. The development of tourism potential is also a follow-up to policies that regulate the overall tourism potential in Samosir Regency, namely Samosir Regent Decree Number 474 of 2017 concerning Determination of Criteria and Classification of Tourism Objects in Samosir Regency. This policy aims to make it easier to classify tourism potential in Samosir Regency, including those in the Pusuk Buhit Area